Faktor-Faktor Yang Mempengaruhi Loyalitas Karyawan (Studi Pada PT Midi Utama Indonesia Tbk. Branch Manado) - Pitoy, Tesalonica I.; Pio, Riane J.; Rumawas, Wehelmina (Productivity, 2020)
This study aims to determine what factors are more influential on employee loyalty. Some of the factors measured in this study are compensation, work environment, career development, work experience, leadership and job characteristics. The sample in this study were 60 respondents who were determined to come from the head office of the Manado branch of PT Midi Utama Indonesia. By using factor analysis, four factors were found to be the highest contributors to employee loyalty in sequence, namely leadership style, job characteristics, work environment, and career development. To make employees continue to have high loyalty to the company, it is hoped that management can maintain the factors that have a strong influence on employee loyalty and increase other factors so that balance can occur, so that employees have a higher level of loyalty to the company.